Bridge modification 2 stronger and safer bridges : proceedings of the international conference organized by the Institution of Civil Engineers and held in London on 7 November 1996 - Pritchard, Brian (Thomas Telford, 1997)
Changes in vehicle weight limits and revisions to safety standards inevitably increase the demands placed on bridges. Increases in traffic flow seen over the past years also mean that many bridges are carrying much greater loads than their designers ever anticipated. Following from the very successful Bridge Modification conference in 1994, this volume contains papers describing the current issues, thinking and technology behind the assessment and improvement of existing bridges.The papers are grouped under the headings: policy; improved assessment; and case studies. In addition to these valuable state-of-the-art papers, this volume reports the equally valuable discussions which ensued. The modification of bridges, inparticular their strength and safety, offers a cost effective solution to maintaining an effective highway infrastructure and meeting the transport needs of the future. This volume will provide an important reference for the many bridge engineers now engaged in this vital work.